The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/ocr.12264
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term pharyngeal airway space changes after mandibular advancement surgery in Class II patients—a two‐dimensional retrospective study

Abstract: Structured Abstract Introduction Planning successful treatment for the correction of anatomic abnormalities of the upper airways, by surgical advancement of the mandible, depends on extensive knowledge of the pharyngeal airway space (PAS). However, there is limited scientific evidence about changes in PAS after mandibular advancement surgery. Aim To evaluate the immediate changes in superior posterior airway space (SPAS) in Class II patients, after mandibular advancement surgery. Materials and Methods A cephal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Twenty papers were finally included in the SR 32‐51 . The data extracted from the included papers are reported in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty papers were finally included in the SR 32‐51 . The data extracted from the included papers are reported in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies evaluated the oropharyngeal anteroposterior linear changes: twelve studies [33][34][35][36][38][39][40][43][44][45]47,51 reported significant changes, four studies 37,41,48,50 observed non-significant findings and one study 32 revealed an increase in the linear oropharyngeal dimension (>2 mm), but not dedicated statistics was run. The MA of the short-term anteroposterior linear measurements of the oropharynx showed statistically significant increase at the level of the posterior border of the tongue (SMD: 0.52, CI: 0.21, 0.84, P = .001; I 2 : 60.5%), of the Gonion (SMD: 1.24, CI: 0.56, 1.91, P < .001; I 2 = 88.8%) and of the second cervical vertebra (SMD: 0.92, CI: 0.14, 1.70, P = .021; I 2 : 88.7%) (Figure 6).…”
Section: Oropharynxmentioning
confidence: 99%
“…The alternative to the method used for cephalometric assessment would be cone beam computed tomography. However, the potential benefits of diagnosis and treatment planning do not outweigh the potential risks of an increase in radiation dose [ 10 , 18 ]. Moreover, further studies should be carried out with larger samples and follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…This device has six connectors of different lengths with the aim of inducing mandibular advancements of 65% to 75% in the maximum protrusion of each patient. This device also allows limited laterality and mouth opening movements [ 10 ] ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation